Funding research in Africa : landscapes of re-institutionalisation - (:unkn) unknown (My University, 2022)
This article begins with an overview of recent and current trends in scientific output in Africa. The focus is on how global dynamics and foreign funding support are directly affecting structural aspects of scientific research. It examines the fundamental role of foreign programmes and new forms of academic cooperation in African science. This includes a discussion of multilateral or transcontinental agreements and local universities, the role of private philanthropy and public institutions, trends in domestic expenditure on research and innovation, and how these are linked to the recent positive upturn in scientific production in many African countries.
Keywords: African Research